Study of Heating Rate Effect on Thermoluminescence Glow Curves of LiF: Mg, Cu, P - Bui Thi, Hong; Anh Hung, Vu; Quang Mien, Nguyen; Loat, Bui Van (VNU Journal of Science: Mathematics - Physics; Vol 34 No 1DO - 10.25073/2588-1124/vnumap.4222, 2018)
The samples of LiF: Mg,Cu,P powder (xeri: GR-200) were irradiated by the gamma radiation  resource with varied exposed dose. The glow curves of thermoluminescence (TL) material were observed with the defferent heating rates. The influence of heating rate on the thermoluminescence property of LiF: Mg,Cu,P was analyzed. The results showed that as the heating rate increases, the peak intensity at the maximum decreases and shifts to higher temperature. The thermoluminesecnce sensitivity of the material also changes and has the optimal value at 6oC/s. This value is also adaptable for measurement of natural environmental and archaeologicaldose.